THE MYTH OF THE INDEPENDENT JUDICIARY - Avramović, Dragutin; Јованов, Илија (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The authors insist that clear terminological and conceptual denotation of the independent judiciary is a necessary precondition in avoiding many misunderstandings. After analysis of different theoretical and practical solutions in performing the separation of powers, the authors claim that its pure form was never and nowhere possible to achieve. Therefore, one cannot speak about independent judiciary which is completely free from political influence, particularly not in terms of the process of judges’ selection. Differently from institutional independence of judiciary (independence of the political branches), which is not possible to reach, the same notion – independence of judiciary, should primarily comprehend individual independence of judge within the decision-making process in particular, concrete cases. In other words, it denotes guarantees which serve to achieve independence in judging (such as permanent judicial tenure, limited removal conditions, salary insulation, etc.). The authors claim that notional and conceptual blurring by distinguishing different dimensions of the independent judiciary is a result of transforming of an important value of rule of law into a tool of ideological (mis)use. Judiciary is in any case institutionally dependent, and the only issue is whether it will be dependent on the state (its legitimate representatives) or on different non-governmental actors who try to interfere the very substance of the independent judiciary, namely independence in decision making by the judge. Therefore, a kind of terminological and conceptual stratification of the independent judiciary is performed by promoting a term which would be more adequate for the factual situation: it is “impartial judiciary” rather than a quite vague “independent judiciary”.